Faster‐acting insulin aspart provides faster onset and greater early exposure vs insulin aspart in children and adolescents with type 1 diabetes mellitus - Fath, Maryam; Danne, Thomas; Biester, Torben; Erichsen, Lars; Kordonouri, Olga; Haahr, Hanne (Pediatric diabetes, 2017)
Background Faster‐acting insulin aspart (faster aspart) is insulin aspart (IAsp) in a new formulation with additional excipients (L‐arginine and niacinamide). In adults, faster aspart provides faster onset and greater early exposure and action vs IAsp. Aim This randomized, double‐blind, 2‐period crossover trial investigated the pharmacological properties of faster aspart vs IAsp in 12 children (6‐11 years), 13 adolescents (12‐17 years), and 15 adults (18‐64 years) with type 1 diabetes mellitus. Methods Subjects received 0.2 U/kg subcutaneous dosing (mean of 8.3, 12.8, and 15.6 U, respectively) immediately prior to a standardized meal (17.3 g carbohydrate/100 mL; amount adjusted by body weight). Results Consistently across age groups, onset of appearance occurred approximately twice‐as‐fast (5‐7 minutes earlier) and early exposure (AUCIAsp ,0‐30min; area under the IAsp curve from 0 to 30 minutes) was greater (by 78%‐147%) for faster aspart vs IAsp, with no treatment differences in total exposure (AUCIAsp ,0‐t) or maximum concentration (C max). Two‐hour postmeal plasma glucose excursion was reduced for faster aspart vs IAsp (although only reaching statistical significance in children). In accordance with the absolute dose administered for each age group, AUCIAsp ,0‐t for faster aspart was lower in children (estimated ratio children/adults [95% confidence interval]: 0.59 [0.50;0.69], P < .001) and adolescents (0.78 [0.67;0.90], P = .002) vs adults. No age group differences were seen in C max (0.91 [0.70;1.17], P = .445, and 0.99 [0.77;1.26], P = .903). The age effect on AUCIAsp ,0‐t and C max did not differ statistically significantly between treatments. Faster aspart and IAsp were well‐tolerated. Conclusion The current findings in children and adolescents suggest a potential for faster aspart to improve postprandial glycemia over current rapid‐acting insulins also in younger age groups. http://ClinicalTrials.gov identifier: NCT02035371.